The Symmetry Comparison balance Performance and Plantar pressure Distribution in Active Adolescent’s Girls with Ankle Pronation While Standing and Stance Phase of Gait: Symmetry Comparison Balance performance and plantar pressure Distribution in Active adolescent’s female with Ankle Pronation while standing and Stance phase of Gait - koreili, zahra; Fatahi, Ali; Azarbaijany, Mohammad Ali; Sharifnezhad, Ali (Journal of Clinical Physiotherapy Research, 2021)
Introduction: The foot-ankle ankle has the capability to perform specific functions such as the weight bearing of body in the standing position against the gravity, moving the body to the front and creating stability to keep the balance and control the posture. The purpose of the present study was to evaluate symmetry comparison of balance performance and plantar pressure distribution in active adolescent’s girls with ankle over pronation while standing and during stance phase of gait. Materials and Methods: In this quasi- experimental study, 34 active adolescent girls between 14 and 17 were selected as simple. The navicular drop measurement by Bordy method, the plantar pressure distribution by foot pressure device (PT-Scan4452F100), and the symmetry between the two limbs and balance function by symmetry Index and Balance performance formula were used. Mean and Deviation was used to describe data, Shapiro-Wilk Test to verify the normality od the data, and independent t-test to compare the variable of the two groups at significance level of P≥0.05. Results: The symmetry comparison of balance performance and plantar pressure distribution showed that a significant difference in symmetry of rear foot pressure distribution (P=0.04), symmetry of rear foot impulse (P=0.04), symmetry of medial heel (P=0.04), symmetry of tars 1 (P=0.04) and symmetry of ankle rotation (P=0.03) between two groups, indicating more symmetry in healthy girls than those ankle hyperpronation, indicating more symmetry in healthy girls than those ankle hyperpronation. Conclusion: The current study’s findings showed that the girls with the hyperpronation had less asymmetry on the medial heel foot and increased pressure distribution on the 1st tarsus. Also, the symmetry of balance function of heel rotation around the ankle’s axis and the impulse of rear foot in the healthy group were more than in the hyperpronation group. Furthermore, because of more contact of the inner surface of the soles with the ground in the people with hyperpronation, the pressure level on the inner edge and 1st metatarsus was increased and the medial heel symmetry in the pronation group was decreased compared to the healthy group. Hence, more scientific evidence is needed to generalize the results.